Challenges of SME in The Tourism Industry: A review - Adilah Md Ramli; Putriku Nuraishah Khairanni Asby; Harifah Mohd Noor; Teuku Afrizal Teuku Anuar (AMER ABRA cE-Baby e-International Publishing House, Ltd, 2022)
One of the local economies in the tourism industry is small and medium entrepreneurs (SMEs). In 2020, data on the tourism industry worldwide decreased because of restrictions on the entry of tourists. This study aims to dig up on the challenges of SMEs through literature studies. The method used is to review and analyze all extant articles published in Google Scholar from 2017 to 2021. Articles will be analyzed by the keywords: SMEs, Challenge, and Tourism. Based on the findings, the challenges faced by SMEs are categorized into internal and external factors such as lack of knowledge and government.